The Influence of Discipline and Leadership on Employee Motivation - Fatonah, Feti; Artadarma, Nyoman; Lintang, Randhitya; Okta Dwipayana, I Made; Marshelina Simanjuntak, Tia (Cipta Kind Publisher, 2024)
The purpose of this study is to explore the impact of discipline and leadership on employee motivation in the work environment. Discipline and leadership are considered crucial factors that can affect the level of individual work motivation in an organization. This research is applied through literature review methods and qualitative approaches by collecting and analyzing data from previous studies. Research findings show that the level of discipline and leadership has a positive and significant influence on employee motivation. This indicates that employees who have a high level of discipline tend to show high levels of work motivation, as well as employees who are under effective leadership. By implication, the study can help organizations to develop management policies and practices that support higher levels of work motivation, with an emphasis on improving discipline and optimal leadership roles. In addition, the study provides a basis for advanced research that can explore in greater depth the specific aspects of discipline and leadership that have the most significant impact on work motivation. At a further level, the study also provides new insights and a deeper understanding of the dynamics of the relationship between such factors in the context of the modern work environment.